1929
DOI: 10.1177/003591572902200738
|View full text |Cite
|
Sign up to set email alerts
|

Discussion on Vertigo

Abstract: Symptoms revealing a state of consciousness, attributable to incoördination of afferent impulses connected with the vestibular system—disturbances of muscle-sense—vestibular ocular tracks—vestibular-spinal tracks. Different Vertigo-Complexes.—Destructive lesions of labyrinth, or of vestibular tracks, partial or complete.—Heterogeneous stimulations of the paired intact vestibular-end organs.—The hypersensitive labyrinth.—Clinical manifestations of vertigo, associated with nausea, headache, visual disturbances,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1934
1934
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…18). Spoendlin's observations (Spoendlin, 1967, 1969, 1972, 1979a, b, 1981) revealed that the Type I neurons had large, myelinated cell bodies and in adult animals only innervated the inner hair cells (Figs. 15, 16) while the Type II neurons possessed small, unmyelinated cell bodies and only innervated the outer hair cells (Figs.…”
Section: Anatomy Of the Membranous Labyrinthmentioning
confidence: 98%
See 1 more Smart Citation
“…18). Spoendlin's observations (Spoendlin, 1967, 1969, 1972, 1979a, b, 1981) revealed that the Type I neurons had large, myelinated cell bodies and in adult animals only innervated the inner hair cells (Figs. 15, 16) while the Type II neurons possessed small, unmyelinated cell bodies and only innervated the outer hair cells (Figs.…”
Section: Anatomy Of the Membranous Labyrinthmentioning
confidence: 98%
“…Heinrich Spoendlin (Spoendlin, 1967) studied the distribution of the afferent and efferent nerve fibers in the organ of Corti of the cat and observed that the bases of outer hair cells were innervated primarily by efferent nerve fibers and that the number of efferent terminals associated with each outer hair cell was greater in the basal turn than in the apex. Iurato et al (1978), Spoendlin (1979a), and Warr (1980) demonstrated by different approaches that the majority of efferent nerves that innervate the outer hair cells originate from large neurons in the contra‐lateral accessory olivary nucleus, whereas the efferent nerves that innervate the inner hair cells originate from small neurons in the homo‐lateral main superior olivary nucleus. Dunn and Morest already (Dunn and Morest, 1975) observed that the afferent fibers innervating the outer hair cells had a different function than the afferent nerves that innervate the inner hair cells.…”
Section: Biology Of the Membranous Labyrinthmentioning
confidence: 99%
“…The original M6ni6re case, which I have taken the trouble to look up, came to autopsy, and a plastic lymph exudate was found, which Scott [3] has convinced himself was a serous meningitis due to acute infective labyrinthitis, where the drum had not perforated. Before M6ni6re had found that vertigo originated in the labyrinth itself, the symptom was always looked on as a forerunner of apoplexy.…”
mentioning
confidence: 99%
“…Asymmetry between the conditions of the two ears and the resulting heterogenous stimuli should never be lost sightlof. Scott [3] finds that lack of patency of the eustachian tubes and invagination of the tympana, unequal on the two sides, is a most fruitful cause. If both tubes are equally inefficient and both tympanic membranes equally depressed, one finds deafness but not vertigo.…”
mentioning
confidence: 99%